Individual-related factors associated with treatment adherence among hypertensive patients - Mohammed Malih Radhi; Shatha Mahmood Niay; Sameeha Naser Abed (AOSIS, 2023)
Background. Currently, some of the most prevalent illnesses are attributable to external sources, such as chronic disorders that threaten people's health. The goal of the study was to investigate the differences in individual characteristics associated with treatment adherence among hypertension patients. Materials and Methods. In this descriptive cross-sectional study, 176 hypertensive patients who reviewed primary healthcare facilities in Babylon Province were included. Experts were used to ensure the study questionnaire's validity, and a pilot study was used to ensure its reliability. Using a standardized questionnaire and interviewing methods, data were collected and analyzed. Results. According to the study's findings, participants' average ages were 59 (10.86), 67% of them were over 60, 55.1% and 65.3% of them were men and married respectively, nearly half of them had moderate monthly income, the unemployed percentage was 61.9%, and 36.4% had completed their secondary education. Two-thirds, or 70.5%, of hypertension patients, reported poor treatment adherence. Ages 30-59, male patients, married, highincome, and college-educated patients showed significantly better treatment compliance (P0.05). Conclusions. Every individual characteristic of patients with high blood pressure is regarded as a predictor of therapy adherence. The current study is one of the few in Iraq to evaluate treatment adherence and look into the various elements that may influence it using the survey approach. Future research on the subject of antihypertensive treatment adherence in the hypertensive population in Iraq employing a representative sample, a qualitative methodology, and more factor exploration may offer additional insights.